Analisis Struktur Rangka Kaku pada Gedung Hotel Wyndham Palembang - Lestari, Endang Sri; Asysyauki, Akhmad Hamdi; Pratama, Muhamad Bagas Wahyu; Zikri, Ridho Anzalla (Jurnal TekstuReka, 2024)
A building that is sturdy, strong, secure, and effective must be designed according to building criteria from all structrural components, starting from columns, beams, floor plates, stairs, foundation, excavations, and basement structures. To build quality that meets the criteria from all aspects. Especially the building under study is a high level building that uses a rigid frame structure where the structure is a rigid connection that connect horizontal beams as well as vertical columns then connected to a plane. And all of this works together so that it is likely that this building meets the criteria for multi-story buildings and guarantees the strength of the building structure to meet its functional aspects.